FAKTOR PENYEBAB KESALAHAN PENGGUNAAN HURUF KATAKANA - Ahmad Azhar Kamal; Dian Bayu Firmansyah; Soni Mulyawan Setiana (Janaru Saja Jurnal Program Studi Sastra Jepang, 2017)
This study discusses what are the factors that causing misuse of katakana in high school students. The research method used in this study is qualitative descriptive method. Type of mistake analyzed in this research is the error one with the classification of the cause of the error, such as Over-generalization, ignorance of rule restriction, incomplete application of rule, and false concept hypotesized. result from this study are the students are having difficulties on katakana letters that have similarity form and katakana that have double consonant or known as sokuon on gairaigo vocabulary.